2022
DOI: 10.3390/ijms232315307
|View full text |Cite
|
Sign up to set email alerts
|

Construction of scFv Antibodies against the Outer Loops of the Microsporidium Nosema bombycis ATP/ADP-Transporters and Selection of the Fragment Efficiently Inhibiting Parasite Growth

Abstract: Traditional sanitation practices remain the main strategy for controlling Bombyx mori infections caused by microsporidia Nosema bombycis. This actualizes the development of new approaches to increase the silkworm resistance to this parasite. Here, we constructed a mouse scFv library against the outer loops of N. bombycis ATP/ADP carriers and selected nine scFv fragments to the transporter, highly expressed in the early stages of the parasite intracellular growth. Expression of selected scFv genes in Sf9 cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Thus, the novel antiseptic M250 at a concentration not exceeding 0.1% can be successfully applied for the treatment of microsporidian spores non-sterilely isolated from infected host animals to establish long-term cell cultures infected with these parasites. In our recent studies, we used 0.1% M250 to sterilize Vairimorpha (Nosema) ceranae and N. bombycis spores obtained from artificially infected insects, and these treatments did not affect the intracellular growth of either parasite [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the novel antiseptic M250 at a concentration not exceeding 0.1% can be successfully applied for the treatment of microsporidian spores non-sterilely isolated from infected host animals to establish long-term cell cultures infected with these parasites. In our recent studies, we used 0.1% M250 to sterilize Vairimorpha (Nosema) ceranae and N. bombycis spores obtained from artificially infected insects, and these treatments did not affect the intracellular growth of either parasite [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study on the scFvG4 showed potent inhibitory effects against microsporidia in the cellular level ( 38 , 39 ). Recently, the scFv antibodies against the outer loops of N. bombycis ATP/ADP-transporters could efficiently inhibit the parasite growth in Sf9 cell line ( 40 ). In the current study, we used the spore germination fluid proteins of N. bombycis as immunogens to prepare monoclonal antibody.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted June 27, 2024. ; https://doi.org/10.1101/2024.06.27.600942 doi: bioRxiv preprint silkworms from infection with N. bombycis. Previous studies have shown that the transgenic expression of monoclonal antibody single-chain variable fragments (scFvs) targeting N. bombycis protein in silkworm or host cell lines reduced N. bombycis infection and proliferation [56][57][58]. As host cell apoptosis promotes the clearing of infected cells and reduces the load of N. bombycis, we can express monoclonal antibody scFv against NbSPN14 in silkworm to block the N. bombycis serpin inhibiting host cell apoptosis; as a result, the resistance of the host silkworm to N. bombycis will enhance.…”
Section: Microsporidia Including E Cuniculi Vittaforma Corneae Nosema...mentioning
confidence: 99%